TAFSIR BI AL-RA’YI SEBAGAI SALAH SATU BENTUK PENAFSIRAN ALQURAN - Ba'asyien, Moh. Arsyad (Hunafa: Jurnal Studia Islamika, 2005)
Tafsir bi al-Ra’yi is one of methods employed by ulama in interpreting the Holy Qur’an. The reason for interpreting the Holy Qur’an using  reasoning is that there are many ayahs (verses of the Qur’an) encourage  us to  think . However, some of ulama  prohibit  the use of reason in interpreting the Qur’an because some of  their interpretations are not compatible with the true massage of the Holy Qur’an. Consequently, their interpretation aims at supporting their own interest only.Key word:  Tafsir bi al-Ra’yi,  bentuk penafsiran,  Alquran